Nedd4‐mediated AMPA receptor ubiquitination regulates receptor turnover and trafficking - Lin, Amy; Hou, Qingming; Jarzylo, Larissa; Amato, Steve; Gilbert, James; Shang, Fu; Man, Heng‐Ye (Journal of neurochemistry, 2011)
J. Neurochem. (2011) 119, 27–39. α‐Amino‐3‐hydroxy‐5‐methyl‐isoxazole‐4‐propionic acid receptors (AMPARs) are the primary mediators of excitatory synaptic transmission in the brain. Alterations in AMPAR localization and turnover have been considered critical mechanisms underpinning synaptic plasticity and higher brain functions, but the molecular processes that control AMPAR trafficking and stability are still not fully understood. Here, we report that mammalian AMPARs are subject to ubiquitination in neurons and in transfected heterologous cells. Ubiquitination facilitates AMPAR endocytosis, leading to a reduction in AMPAR cell‐surface localization and total receptor abundance. Mutation of lysine residues to arginine residues at the glutamate receptor subunit 1 (GluA1) C‐terminus dramatically reduces GluA1 ubiquitination and abolishes ubiquitin‐dependent GluA1 internalization and degradation, indicating that the lysine residues, particularly K868, are sites of ubiquitination. We also find that the E3 ligase neural precursor cell expressed, developmentally down‐regulated 4 (Nedd4) is enriched in synaptosomes and co‐localizes and associates with AMPARs in neurons. Nedd4 expression leads to AMPAR ubiquitination, leading to reduced AMPAR surface expression and suppressed excitatory synaptic transmission. Conversely, knockdown of Nedd4 by specific siRNAs abolishes AMPAR ubiquitination. These data indicate that Nedd4 is the E3 ubiquitin ligase responsible for AMPAR ubiquitination, a modification that regulates multiple aspects of AMPAR molecular biology including trafficking, localization and stability.